Book review. Issue 1 (February 2014) - White, Alison
Abstract : A Sonographer's Guide to the Assessment of Heart Disease Bonita Anderson RRP 169.00 ISBN‐13: 9780992322205 Publisher: MGA Graphics 507 pages